YOGA AS AN ANCIENT SCIENCE OF HEALING: ITS IMPACT ON MENTAL HEALTH OF WOMEN - Jiteswori Devi, Naorem; Subrahmanyam, Kambhampati (International Journal of Ayurveda and Pharma Research, 2015)
Since time immemorial Yoga had been practiced in India. It is considered to be a means for physical, mental and spiritual growth of an entity. With increasing research evidence, yoga has been emerging as a powerful tool to achieve good states of health, both at physical and mental levels. Several studies have demonstrated the beneficial effects of yoga on the mental health of women. Yoga improved quality of life and sleep, provided peace of mind, and reduced depression, anxiety levels and psychological symptoms of stress related problems, illness and insomnia, menopausal symptoms and all pains. It also helped breast cancer survivor to achieve psychological well-being. Yoga can be a useful tool for both physical and mental well being for women.